Optimization of Goods Receipt and Issuance at Enseval using Oracle E-Business Suite - Meilynda Yanti, Ni Kadek; Chandra Dewi, Ni Ketut Nadya; Maya Sartika, Rintihani Lodia; Salsabilla , Taffana Wanda; Animah (Jurnal Pengabdian dan Pemberdayaan Banyuwangi (Jurnal Abdiwangi), 2025)
Efficient and accurate inventory management is crucial for supporting the smooth distribution of pharmaceutical and medical device products, especially in large companies such as PT Enseval Putera Megatrading Tbk, Mataram Branch. This community service topic was chosen due to the persistent challenges in stock recording, early detection of expired products, and the suboptimal implementation of cycle counts and stock opname. The service method involved training, mentoring, and hands-on practice for warehouse and finance accounting staff in using the Oracle E-Business Suite. The activities began with problem identification, preparation of training materials tailored to the partner’s needs, implementation of both classroom and on-site training, followed by monitoring and evaluation of the results. The outcomes showed improvements in inventory recording accuracy, a reduction in discrepancies between physical and system stock data, and enhanced staff capability in detecting and handling expired products. Additionally, there was a noticeable shift in staff attitudes, becoming more adaptive to digitalized work processes and the adoption of new SOPs. These achievements demonstrate that strengthening human resource capacity through structured training and the use of information technology is essential for increasing efficiency and accountability in inventory management. In conclusion, the results of this community service are expected to serve as a model for developing inventory management systems in other distribution companies and to encourage further digital transformation in the logistics and pharmaceutical sectors